The Effect of Alcohol on the Canadian Constitution ... Seriously - Fish, Morris (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
Alcohol has exerted a staggering influence on the Canadian constitution. It was a prominent feature of daily life in the young Dominion, much to both the delight and chagrin of many. The temperance movement exerted its own influence on both the federal and provincial legislatures. Without “alcohol” as a head of power, the legislatures claimed control over this seeming, social evil sometimes under “Peace, Order and Good Government”, “criminal law”, or “Trade and Commerce”; at other times under “Property and Civil Rights”, “Local Matters”, and so forth. Court challenges abounded; the result was, in part, the judiciary’s failure to walk a straight line toward a clear division of powers between the federal and provincial governments. But the result was also many of the doctrines of division of powers that still form part of Canadian constitutional law. Beyond its impact on the division of powers, alcohol was also at the root of Canada’s most important decision on the rule of law: Roncarelli—a decision argued and won by the late F. R. Scott.